12th International CHARGE syndrome conference proceedings. Issue 4 (11th January 2016) - Martin, Donna M.; Salem‐Hartshorne, Nancy; Hartshorne, Timothy S.; Scacheri, Peter C.; Hefner, Margaret A.
Abstract : The CHARGE Syndrome Foundation holds an International conference for families and professionals every other summer. In July, 2015, the 12th meeting was held in Schaumburg, Illinois, at the Renaissance Schaumburg Hotel. Day one of the 4‐day conference was dedicated to professionals caring for and researching various aspects of CHARGE, including education, medical management, animal models, and stem cell‐based approaches to understanding and treating individuals with CHARGE. Here, we summarize presentations from the meeting, including a synopsis of each of the three different breakout sessions (Medical/Clinical, Basic Science/CHD7, and Education), followed by a list of abstracts and authors for both platform and poster presentations. © 2016 Wiley Periodicals, Inc.